Some discourse-interactional uses of yinwei 'because' and its multimodal production in Mandarin conversation. (November 2016) - Li, Xiaoting
Abstract: Yinwei 'because' is a causal conjunction or preposition introducing clauses or NPs of reason or cause in Mandarin. In addition to its use as causal connective, yinwei seems to have other discourse-interactional functions. Adopting the methodology of conversation analysis and interactional linguistics, this study explores some discourse-interactional uses of yinwei in Mandarin face-to-face conversation. An examination of the data shows that one type of yinwei recurrently occurs after the possible completion of a sequence, connecting the subsequent utterances to the talk prior to the immediately preceding one. Specifically, it occurs in two sequential and interactional environments: after the possible completion of a recipient-initiated sequence that may change the ongoing (focus of the) topic, and after the possible closure of a storytelling. In each environment, yinwei is produced with particular prosodic and bodily-visual features and implements particular interactional tasks. This study shows that yinwei has fine-grained interactional functions of building (courses of) actions, organizing sequences and discourse, and accomplishing interactional tasks in Mandarin conversation. Highlights: yinwei 'because' has discourse-interactional functions in Mandarin conversation. yinwei connecting subsequent utterances to the pre-prior talk. yinwei reopens a storytelling. yinwei is used to pursue interactional agenda and recipient's affiliative responses. Prosodic and bodily-visual features in the production of yinwei .